ANALYSIS AND COMPREHENSIVE EVALUATION OF FINANCIAL INSTITUTIONS IN TERMS OF ECONOMIC MODERNIZATION - Zhurynov G. M.; Kazanbayeva Zh. S.; Turakulova L. R.; Lutfullaуevа R. A.; Shalbaуeva А. Р. (Scientific Journal of Pedagogy and Economics, 2021)
Active transformation processes of globalizing world finance, new goals and objectives of modernization of the national financial system determine the need to form an effective financial system in Kazakhstan that can withstand external challenges and ensure the stable development of the country and its internal market in the context of globalization. The modern financial system is a complex set of interrelated and interacting institutions, financial instruments, mechanisms and procedures aimed at ensuring the financial activities of economic entities and other entities (in particular, public law, etc.) that create conditions for ensuring reproduction processes. In practice, the process of globalization associated with global financial and economic integration is becoming more active with the strengthening of supranational regulation of the world economic space. The study of problems of financial and credit aspects of economic modernization in the conditions of globalization as a scientific direction is under development and scientific discuss, this is due to the fact that it is an unfolding process, but not yet a fait accompli, and the problems that confronted the state in the age of globalism, extremely important and require a constant updating of strategy of development with a predominance of the innovative aspect as the most effective in new economic conditions. The purpose of the study. The aim of the study is to clearly identify the problems of financial and credit aspects of economic modernization in the context of globalization and ways to solve them. Methods of analysis of the scientific and information base, synthesis of the obtained data into theoretical conclusions and practical recommendations, methods of economic analysis were used as tools. The scientific novelty of the research consists in the development of provisions that form the theoretical and methodological basis for determining the financial and credit aspects of economic modernization in the context of globalization